THE APPLICATION OF EOQ METHOD IN PROCURING RAW MATERIALS OF TOBACCO STOCK AT PT. CAKRA GUNA CIPTA MALANG - Surya, Maulana Eka (Jurnal Ilmiah Mahasiswa FEB, 2017)
Operational activities in the process requires proper planning in order to achieve the company’s established goals. One component in the company’s operations that require planning to support its operational activities is inventory. PT. Cakra Guna Cipta Malang as a company producing cigarettes needs tobacco as raw material for its production. Procurement by the company results in too many ordering frequencies causing a large total inventory cost. The purpose of this research is to see how the difference in total inventory cost calculation after the application of EOQ method. This research uses winter’s method forecasting to calculate the estimated needs of tobacco in the next period. This research also calculates the optimal supply quantity in procuring tobacco, re-order point, and safety stock needed to anticipate fluctuations in demand for tobacco raw materials needs.Keywords : Economic Order Quantity (EOQ), Reorder Point (ROP), Safety Stock, Forecasting Winter’s Method.